Genomic Analysis of Putative Virulence Factors Affecting Cytotoxicity of Cronobacter - Cui, Jinghua; Hu, Jinrui; Du, Xiaoli; Yan, Chao; Xue, Guanhua; Li, Shaoli; Cui, Zhigang; Huang, Hua; Yuan, Jing (Frontiers in Microbiology, 2020)
Cronobacter spp. can cause systemic infections, such as meningitis, sepsis, and necrotizing enterocolitis, in immunocompromised patients, especially neonates. Although some virulence factors have been reported previously, the pathogenesis of Cronobacter remains unclear. In this study, we compared genome sequences from different Cronobacter species, sequence types, and sources, with the virulence genes in the virulence factor database. The results showed that Cronobacter has species specificity for these virulence genes. Additionally, two gene clusters, including sfp encoding fimbriae and hly encoding hemolysin, were discovered. Through cell adhesion, cytotoxicity, and hemolysis assays, we found that the isolates possessing the two gene clusters had higher cytotoxicity and stronger hemolysis capacity than those of other isolates in this study. Moreover, analysis of type VI secretion system (T6SS) cluster and putative fimbria gene clusters of Cronobacter revealed that T6SS have species specificity and isolates with high cytotoxicity possessed more complete T6SS cluster construction than that of the rest. In conclusion, the two novel gene clusters and T6SS cluster were involved in the mechanism underlying the cytotoxicity of Cronobacter.